Sleep disturbances in patients with lung cancer in Turkey - YUMUK, PERRAN FULDEN (TURKISH ASSOC TUBERCULOSIS & THORAX, 2018)
Introduction: Sleep quality is known to be associated with the distressing symptoms of cancer. The purpose of this study was to analyze the impact of cancer symptoms on insomnia and the prevalence of sleep-related problems reported by the patients with lung cancer in Turkey. Materials and Methods: Assesment of Palliative Care in Lung Cancer in Turkey (ASPECT) study, a prospective multicenter study conducted in Turkey with the participation of 26 centers and included all patients with lung cancer, was re-evaluated in terms of sleep problems, insomnia and possible association with the cancer symptoms. Demographic characteristics of patients and information about disease were recorded for each patient by physicians via face-to-face interviews, and using hospital records. Patients who have difficulty initiating or maintaining sleep (DIMS) is associated with daytime sleepiness/fatigue were diagnosed as having insomnia. Daytime sleepiness, fatigue and lung cancer symptoms were recorded and graded using the Edmonton Symptom Assessment Scale. Results: Among 1245 cases, 48.4% reported DIMS, 60.8% reported daytime sleepiness and 82.1% reported fatigue. The prevalence of insomnia was 44.7%. Female gender, patients with stage 3-4 disease, patients with metastases, with comorbidities, and with weight loss > 5 kg had higher rates of insomnia. Also, patients with insomnia had significantly higher rates of pain, nausea, dyspnea, and anxiety. Multivariate logistic regression analysis showed that patients with moderate to severe pain and dyspnea and severe anxiety had 2-3 times higher rates of insomnia. Conclusion: In conclusion, our results showed a clear association between sleep disturbances and cancer symptoms. Because of that, adequate symptom control is essential to maintain sleep quality in patients with lung cancer.
Keywords: Lung cancer; sleep disturbance; insomnia; symptom; pain; dyspnea; QUALITY-OF-LIFE; SYMPTOMS; PAIN